A viable equity mechanism for all? Exploring the diversity of entry requirements and supports in Australian enabling education. Issue 5 (29th July 2021) - Baker, Sally; Ulpen, Tamra; Irwin, Evonne Lee
ABSTRACT: Enabling education is an enactment of Australia's attempts to address inequity in higher education (HE), offering free, alternative pathways to students who do not enter through the 'traditional' school–university pathway. Each Australian enabling program is different in terms of size, design, curricula and length, meaning that there is significant national variation. This is particularly the case with the entry requirements for enrolment. While many enabling programs are 'open', where no entry requirements are mandated, other programs implement prerequisite mechanisms, sometimes administered by diagnostic testing instruments. The supports and resources to meet the diverse learning needs of enabling students also vary at each institution according to program design. Access to (or a lack of) appropriate support can significantly impact on students' academic progress. Drawing from the findings of two national audits of Australian enabling programs, this article explores the benefits and challenges associated with the diverse provision and operation of enabling programs. With a particular focus on the varying approaches to entry and available supports, this article examines how specific learning needs of enabling students are identified, and what type of supports are available for them to achieve positive outcomes in their study and, hence, move on to undergraduate programs. In this article, we argue that the diverse nature of enabling program design and provision complicates understandings of what constitutes 'academic readiness' for students with implications for the transferability of their enabling qualification.